(untitled) (Journal of the College of Basic Education, 2024)
Geographic factors are one of the main factors influencing the development of tourism in Baghdad. It includes geographic location, climate, and topography, in addition to other geographic factors such as political, economic, and social geography. This research aims to study the impact of these factors on the development of tourism in Baghdad and to demonstrate their importance in attracting tourists, and their impact on tourism activities and tourism infrastructure. The study will include a definition of various geographical factors, an analysis of their impact on tourism in Baghdad, and ways to improve the city’s tourism infrastructure